(untitled) (Revista de História Regional, 2007)
The article endeavors to show that the contemporary conceptions of space, territory or region relate, albeit indirectly, to the concept of space as defined in the current theories of natural science, namely the notion that there is no space independent of contents and processes. Also discussed are recent anthropological notions about space and those derived from the idea of a global economy: in which way do such trends change the historians view of space?